2020
DOI: 10.3390/microorganisms8111776
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes of Epstein-Barr Virus-Associated Gastric Carcinoma Suppress Dendritic Cell Maturation

Abstract: The Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) is characterized by the infiltration of lymphocytes and a unique tumor microenvironment. Exosomes from cancer cells are essential for intercellular communication. The aims of this study were to investigate the secretion of EBVaGC exosomes and their physiological effect on dendritic cell maturation in vitro and to characterize dendritic cells (DCs) in EBVaGC in vivo. Western blotting analysis of CD63 and CD81 of exosomes from EBV-infected gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Epstein-Barr virus (EBV)-positive gastric cancer is characterized by an abundance of infiltrated-immune cells, including dendritic cells, but with suppressed anti-tumor immunity. Hinata et al revealed that EBV-positive gastric cancer has more TDE secretion than EBV-negative gastric cancer (58). These TDEs suppress dendritic cell maturation, represented with low CD86 expression, and inhibit activation of other immune cells (58).…”
Section: Inhibition Of Dendritic Cell Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Epstein-Barr virus (EBV)-positive gastric cancer is characterized by an abundance of infiltrated-immune cells, including dendritic cells, but with suppressed anti-tumor immunity. Hinata et al revealed that EBV-positive gastric cancer has more TDE secretion than EBV-negative gastric cancer (58). These TDEs suppress dendritic cell maturation, represented with low CD86 expression, and inhibit activation of other immune cells (58).…”
Section: Inhibition Of Dendritic Cell Maturationmentioning
confidence: 99%
“…Hinata et al. revealed that EBV-positive gastric cancer has more TDE secretion than EBV-negative gastric cancer ( 58 ). These TDEs suppress dendritic cell maturation, represented with low CD86 expression, and inhibit activation of other immune cells ( 58 ).…”
Section: Roles Of Exosomes In Gastric Cancer Pmn Formationmentioning
confidence: 99%
“…This Special Issue assembles eleven papers, comprising seven research articles, two reviews, and two brief reports, which collectively provide novel information on the mechanisms of oncogenesis [ 2 , 3 , 4 , 5 , 6 ] and viral replication [ 7 , 8 , 9 , 10 ], as well as applications for diagnosis [ 11 , 12 ].…”
mentioning
confidence: 99%
“…Using a variety of methods and approaches, several studies have provided a novel notion in understanding how EBV contributes to the development of various tumors, including GC [ 2 , 3 ], HL [ 4 ], NPC [ 5 ], and oral squamous cell carcinoma [ 6 ], on a molecular basis. A distinct feature of EBV-associated GC is the significant infiltration of immune cells in the epithelium, which appears to establish a unique tumor microenvironment.…”
mentioning
confidence: 99%
See 1 more Smart Citation